Analysis of RANK/RANKL expression in metastatic and non-metastatic breast cancer: Systematic literature review (Research, Society and Development, 2025)
Breast cancer is the most frequent cause of death from cancer in the female population worldwide and the clinical management of these patients represents a challenge, given the variety of disease progression profiles. The presence of distant metastasis has a major impact on patient survival, with bone metastases being the most common. The RANK/RANKL/OPG system is identified as a signaling pathway involved in the maintenance of bone homeostasis and mammary gland development. The investigation of the association between the biomarkers expression of receptor activator of nuclear factor kappa B (RANK) and binding protein (RANKL) in the prognostic and predictive assessment of breast cancer helps in the discussion of the use of denosumab in the prevention of bone metastases and in the treatment of the disease. This study aims to present a systematic review on the analysis of RANK/RANKL expression in metastatic and non-metastatic breast cancer. Eight studies totaling 1876 patients were included, and six of the studies demonstrated associations between the occurrence of more aggressive tumors, the metastatic potential of breast cancer, the emergence of bone metastases and, mainly, a worse prognosis in survival curves. The studies included in this review confirm the predictive and prognostic importance of RANK in the evaluation of patients with breast cancer, reaffirming the need for more homogeneous studies for the adequate use of therapeutic and preventive protocols that use this marker as a therapeutic target.